Clergy and community - Wilton, A; Wilton, Alene Jayne (1998)
﻿ The intention of this thesis is to make a contribution to the understanding of the eighteenth-century Church of England within the community in which it existed. Recognising the enormous variation that existed within the Church during the period, this study provides a close comparison of two archdeaconries, (something which is rarely undertaken in the historiography of the Church), both of which have never received attention from historians. In order to study the Church in these regions, the archdeaconries of Buckingham and Gloucester, detailed consideration is given to the role and activities of the parochial clergy in each archdeaconry. By concentrating upon the community, and the clergy's place within it, this thesis is able to provide a detailed picture of the social, political and economic integration of the clergy within these two specific regions, as well as their pastoral work and family life, the latter much neglected by historians. It devotes much attention to the property of the clergy, as a means of locating the clergy within local communities, and because of the great effect their property and income had upon other spheres of their everyday life. In doing this, this thesis demonstrates the diversity of experience of clergy within each archdeaconry, but it also shows some overall trends which marked the experience of parochial clergy in the period. It argues that the eighteenth-century clergyman was immersed in almost every aspect of community life, and although conscious of his distinctiveness as a parson, such integration represented a fusion of the ecclesiastical and secular, the incumbent's pragmatic response to the circumstances of the community of which he was a part.